PERANCANGAN DESAIN UI/UX WEBSITE KASIR TOKO SEMBAKO DENGAN METODE USER CENTERED DESIGN (UCD) PADA UD JAYA ANUGRAH - Aisyah Yasmin Tanjung; Hermansyah; Heri Kurniawan (Jurnal Nasional Teknologi Komputer, 2026)
The current era of digitalization has transformed the way various business sectors operate, including retail and commerce. Grocery stores, as one of the business units in the retail and commerce sector, are directly involved in meeting the daily needs of the community. As such, grocery stores are required to adapt to the development of information technology to improve operational efficiency and customer service. UD Jaya Anugrah is a grocery store located in Medan. In its operations, transaction processes and inventory management are still carried out manually using a conventional cashier system. This has led to various problems, such as difficulties in recording transactions, managing stock, creating reports, and limitations in providing accurate information to business owners. Therefore, to improve its workflow, it is necessary to add a software tool that can run the sales system effectively. To create this software, a prototype of User Interface (UI) and User Experience (UX) is required. The method used in this research is the User Centered Design (UCD) method. Through the UCD method, researchers hope that when users interact with the application, they can easily understand the existing functions and use them smoothly.